Mass attenuation Coefficient and Total cross-section Area of Platinum Group Composition - Das, Santos Kumar; Dhobi, Saddam Husain (Patan Prospective Journal, 2023)
Radiation shielding is a critical practice involving the utilization of materials or barriers to safeguard against ionizing radiation by absorbing, scattering, or blocking the radiation. Its primary objective is to curtail exposure and mitigate potential health risks associated with radiation. In diverse fields like medicine, industry, and nuclear applications, radiation shielding materials play a pivotal role in ensuring the safety of individuals and equipment, contributing significantly to the maintenance of secure environments. This study focuses on characterizing materials for radiation shielding, particularly of Platinum group alloys in varying compositions with hydrogen. Using the Klein-Nishina (KN) formula, the investigation calculates electronic cross-sections (ECS), total mixture cross-section (TMCS), and mass attenuation coefficient (MAC) for different weight percentages of Platinum group alloys (0.1 to 0.6) when exposed to γ-ray photons of various energies. The outcomes emphasize the strong dependence of these cross-sections and MAC on photon energy and the charge number of the material, revealing a decrease with increasing photon energy and an increase with the charge number to mass number ratio (Z/A). The research underscores that fundamental parameters such as charge number, photon energy, and Z/A can be manipulated to enhance the utility of these elements in radiation shielding, protection, dose measurements, and imaging. The study's implications extend to the optimization of Platinum Group alloy compositions, offering insights for the development of tailored materials with enhanced shielding effectiveness in radiation protection and safety applications.